Impact of Hematocrit on Coagulation Measured by Rotational Thromboelastometry in Healthy Subjects and Patients with Polycythemia - Martin, Marie; Nader, Elie; Rezigue, Hamdi; Dargaud, Yesim; Renoux, Céline; Joly, Philippe; Heiblig, Mael; Nougier, Christophe; Connes, Philippe (Seminars in Thrombosis and Hemostasis, 2025)
Thrombotic and cardiovascular events are among the leading causes of death for patients with polycythemia, more specifically for those with primary origin. It has been suggested that the high hematocrit (Hct) would favor hypercoagulability. However, the impact of Hct on coagulation in patients with polycythemia has not been investigated so far. The aim of our study was to compare the coagulation profiles of healthy subjects and patients with polycythemia and to evaluate the in vitro impact of Hct on coagulation. Blood from healthy individuals (n = 100 for blood viscosity; n = 19 for coagulation) and patients with primary/secondary polycythemia (n = 29 for blood viscosity; n = 20 for coagulation) was used to perform measurements at native Hct. The impact of Hct modulation (20% vs. 50%) on coagulation was tested in vitro in 9 healthy subjects and 19 patients with polycythemia. Blood viscosity was measured by viscosimetry and coagulation and fibrinolysis by rotational thromboelastometry. In patients with polycythemia, Hct, and blood viscosity were higher, clotting time was prolonged and clot lysis was faster compared to healthy individuals. Our in vitro results showed that the clotting time was faster and the clot firmness higher at 20% versus 50% Hct for both populations, without any difference between the two populations at a given Hct. Our findings suggest that the interpretation of thromboelastometry results should be approached with caution in patients with high Hct. The in vivo hypercoagulable state of patients with polycythemia is probably the consequence of changes in hemodynamic conditions attributed to blood hyper-viscosity, that may promote venous stasis and platelet margination.
Keywords: hematocrit; thromboelastometry; polycythemia; clot